The Application and Future of Smart Materials in Modern Civil Engineering - Gong, Baichuan (Scientific Journal of Technology, 2026)
The field of civil engineering is undergoing a transformative shift, driven by the integration of advanced materials that possess capabilities beyond traditional concrete and steel. Smart materials, characterized by their ability to sense, respond, and adapt to external stimuli such as stress, strain, temperature, moisture, or magnetic/electric fields, are at the forefront of this revolution. This article provides a comprehensive overview of the major classes of smart materials relevant to civil infrastructure, including piezoelectric materials, shape memory alloys (SMAs), fiber optic sensors, and self-healing concrete. It explores their practical applications in structural health monitoring (SHM), vibration control, seismic retrofitting, and the development of multifunctional, durable infrastructure. The discussion highlights significant benefits such as enhanced safety, reduced lifecycle costs, and improved sustainability. Furthermore, the article addresses the current challenges of high costs, long-term durability validation, and standardization, while outlining a promising future where smart materials are integral to creating resilient, adaptive, and intelligent civil systems.